Chronic atrophic gastritis in different ages in South China: a 10-year retrospective analysis - Zhang, Zefeng; Zhang, Xiaoguang (BMC gastroenterology, 2023)
To explore the prevalence, characteristics, age distribution and etiology changes of chronic atrophic gastritis (CAG) in South China. This study included all patients who underwent endoscopy examinations from 2011 to 2020 in our hospital. Patients were divided into groups 1 (2011-2015) and 2 (2016-2020). The prevalence, characteristics, age distribution and etiology changes of CAG were compared between groups. Overall CAG prevalence was 20.92% (24,084/115,110) from 2011 to 2020; prevalence significantly differed between groups (18.78%, 8468/45,087, in group 1 and 22.30%, 15,616/70,023, in group 2). Patients with CAG had significantly younger age (under 45) and more corpus atrophy and more autoimmune atrophic gastritis (AAG) in group 2 than in group 1. AAG prevalence in group 2 was 30.11% (4702/15,616) significantly higher than 13.57% (1149/8468) in group 1. 82 patients with AAG later exhibited gastric cancer without obvious clinical features over the decade. CAG is increasing and seems starting earlier among people during the study period. We need to focus on diagnosis and treatment of corpus related atrophy and AAG, especially for the young. Laboratory examination, endoscopic biopsy and surveillance are important for CAG.